Recent Advances in the Panel Stochastic Frontier Models: Heterogeneity, Endogeneity and Dependence - Subal C. Kumbhakar; Hung-Pin Lai (International Journal of Empirical Economics, 2022)
This paper primarily reviews the panel stochastic frontier (SF) model in which the composite error term [Formula: see text] has four components, i.e. [Formula: see text] where [Formula: see text] and [Formula: see text] are the persistent and transient inefficiency components, [Formula: see text] is the random firm effect and [Formula: see text] is the random noise. We discuss a variety of model specifications of the four-component SF panel model and estimation approaches developed mostly during the period 2014 to 2021. While discussing these models, we focus on the following issues: heterogeneity, endogeneity of inputs/output(s), inclusion of determinants of inefficiencies via their variances and dependence among the error components. Additionally, we examined models that introduce allocative inefficiency. Models that use both multi-step and system approaches to model allocative inefficiency are also examined.